Amino- and sulfo-bifunctionalized hyper-crosslinked organic nanotube frameworks as efficient catalysts for one-pot cascade reactions. (15th January 2019) - Meng, Guojie; Gao, Shengguang; Liu, Ying; Zhang, Li; Song, Chunmei; Huang, Kun
Abstract : The synthesis of amino- and sulfo-bifunctionalized hyper-crosslinked organic nanotube frameworks for one-pot cascade reactions was reported for the first time. Abstract : In this paper, novel amino- and sulfo-bifunctionalized hyper-crosslinked organic nanotube frameworks (H-ONTFs) were directly prepared by templating core–shell bottlebrush copolymers via a Friedel–Crafts (F–C) alkylation reaction, in which the acidic sites were anchored into the wall of nanotubes and basic sites were introduced onto the inner layer wall of nanotubes through a rational molecular design strategy. The resulting acid–base bifunctionalized H-ONTFs showed excellent catalytic activities for one-pot deacetalization–Knoevenagel cascade reactions due to their open-ended structure, large surface area and good multi-porosity interconnectivity.